2002
DOI: 10.1088/0266-5611/18/6/322
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Lamb wave tomography

Abstract: Nondestructive evaluation (NDE) of aerospace structures using traditional methods is a complex, time-consuming process critical to maintaining mission readiness and flight safety. Limited access to corrosion-prone structure and the restricted applicability of available NDE techniques for the detection of hidden corrosion or other damage often compound the challenge. In this paper we discuss our recent work using ultrasonic Lamb wave tomography to address this pressing NDE technology need. Lamb waves are ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(84 citation statements)
references
References 19 publications
0
84
0
Order By: Relevance
“…A decade later, a research team led by Hinders carried out a number of studies in Lamb wave tomography. Malyarenko and Hinders (2000), Leonard et al (2002) studied a number of time-of-flight tomography algorithms using Lamb waves and provided an extensive bibliography of literature in this research area. Leonard and Hinders (2005) subsequently demonstrated that time-of-flight Lamb wave tomography could be used for inspecting curved panels.…”
Section: Background Of the Proposed Methodsmentioning
confidence: 99%
“…A decade later, a research team led by Hinders carried out a number of studies in Lamb wave tomography. Malyarenko and Hinders (2000), Leonard et al (2002) studied a number of time-of-flight tomography algorithms using Lamb waves and provided an extensive bibliography of literature in this research area. Leonard and Hinders (2005) subsequently demonstrated that time-of-flight Lamb wave tomography could be used for inspecting curved panels.…”
Section: Background Of the Proposed Methodsmentioning
confidence: 99%
“…A tomographic image can be reconstructed by using wave speed, waveform or amplitude as flaw-relevant features. The standard parallel projection, fan-beam or crosshole schemes are usually adopted in tomography technique [36]. The crosshole scheme with iterative nature and great flexibly is more suited for any geometry and incomplete data set.…”
Section: Lamb Wave Methodsmentioning
confidence: 99%
“…In 2000, Malyarenko studied the filtered method for fan beam projection and double crosshole geometry [11]. In 2002, Leonard presented a sample of parallel projection and fan beam projection [12].…”
Section: Transmission Tomographymentioning
confidence: 99%